(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
This review aims to identify the causes that contribute to global warming and offers the most likely cause, according to the published evidence. Additionally, this page provides various mitigation strategies for the global warming issue. The most practical economic and technical solution to the global warming problem is the simultaneous adoption of mitigation and adaptation techniques. Global warming is a major consequence of human activities caused by the excessive use of old fuels as an energy- source, which has caused increased quantities of “greenhouse gases” (GHGs). The atmosphere contains gases that increase the Earth’s average surface temperature, such as carbon dioxide, methane, nitrous oxide, and water vapor. Global warming phenomena have become a global problem with negative effects on various parts of the environment due to the glaciers melting, overflowing carbon dioxide (CO2), and too much warming of aquatic bodies, among others. Generality people are still unaware of global warming and do not see it as a main problem in the coming years.